2023
DOI: 10.1055/a-2020-8717
|View full text |Cite
|
Sign up to set email alerts
|

2,2-Disubstituted Indoxyls via Oxidative Dearomatization: Generalization to 2-Alkylindoles and Application to Alkaloid Synthesis

Abstract: 2,2-Disubstituted indoxyls are commonly found within natural products and bioactive molecules. Among the numerous methods to access such motifs, the dearomative transformation of indoles represents an attractive approach. Despite much development, a potential gap exists in the oxidative union of readily accessible 2-substituted indoles with nucleophilic partners, where a general transformation accommodating 2-alkyl substitution and a broad range of nucleophiles is lacking. Herein, we describe the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 98 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Nitrogen heterocycles are commonly found in natural products and drugs . Dearomatization of indoles to generate indolines has thus received considerable attention. Moreover, dearomatization of indoles using fluorine-containing groups has emerged as an important research topic because fluorine atoms can markedly alter the physicochemical properties and metabolic stability of bioactive molecules .…”
mentioning
confidence: 99%
“…Nitrogen heterocycles are commonly found in natural products and drugs . Dearomatization of indoles to generate indolines has thus received considerable attention. Moreover, dearomatization of indoles using fluorine-containing groups has emerged as an important research topic because fluorine atoms can markedly alter the physicochemical properties and metabolic stability of bioactive molecules .…”
mentioning
confidence: 99%
“…Not surprisingly, a stoichiometric amount of Lewis acid was required to efficiently induce the formation of cyclization product 4 . In this regard, we were gratified to find that the cyclization was accomplished by treatment of 5 with 10 mol % p -TsOH·H 2 O in 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) (entry 5). , A survey of solvents revealed that HFIP is critical for this cyclization (entry 5 vs entries 6–9). While the reaction in 2,2,2-trifluoroethanol (TFE) also proceeded smoothly, the yield of 4 (70%) in the reaction in TFE did not exceed that in HFIP (entry 6).…”
mentioning
confidence: 99%